STRATEGI PEMBELAJARAN INQUIRI - Faizatul Husna (CV. Adiba Aisha Amira, 2024)
This writing aims to explain the Inquiry Learning Strategy. Education is a learning process where a student receives and understands knowledge as part of himself. One of the determinants of the success of the teaching and learning process is how the teacher teaches. The selection and use of appropriate learning approaches, methods or strategies is intended for effective learning to occur. And one learning strategy to provide opportunities for students to discover their own knowledge and play an active role in learning so that they are able to understand concepts well and develop critical thinking skills is the inquiry learning strategy. This research is qualitative research in the nature of a library research using documentation data collection methods and content analysis as the main objects. The approach used by researchers is a descriptive analysis approach. An inquiry learning strategy is a series of learning activities that emphasize the process of thinking critically and analytically to search for and find answers to a problem in question.